Context‐dependent fitness costs of reproduction despite stable body mass costs in an Arctic herbivore. Issue 1 (3rd October 2021) - Pigeon, Gabriel; Albon, Steve; Loe, Leif Egil; Bischof, Richard; Bonenfant, Christophe; Forchhammer, Mads; Irvine, Robert Justin; Ropstad, Erik; Veiberg, Vebjørn; Stien, Audun
Abstract: The cost of reproduction on demographic rates is often assumed to operate through changing body condition. Several studies have found that reproduction depresses body mass more if the current conditions are severe, such as high population densities or adverse weather, than under benign environmental conditions. However, few studies have investigated the association between the fitness components and body mass costs of reproduction. Using 25 years of individual‐based capture–recapture data from Svalbard reindeer Rangifer tarandus platyrhynchus, we built a novel Bayesian state‐space model that jointly estimated interannual change in mass, annual reproductive success and survival, while accounting for incomplete observations. The model allowed us to partition the differential effects of intrinsic and extrinsic factors on both non‐reproductive mass change and the body mass cost of reproduction, and to quantify their consequences on demographic rates. Contrary to our expectation, the body mass cost of reproduction (mean = –5.8 kg) varied little between years (CV = 0.08), whereas the between‐year variation in body mass changes, that were independent of the previous year's reproductive state, varied substantially (CV = 0.4) in relation to autumn temperature and the amount of rain‐on‐snow in winter. This body mass loss led to a cost of reproduction on the next reproduction, which was amplified by the same environmental covariates, from a 10% reduction in reproductive success in benign years, to a 50% reduction in harsh years. The reproductive mass loss also resulted in a small reduction in survival. Our results show how demographic costs of reproduction, driven by interannual fluctuations in individual body condition, result from the balance between body mass costs of reproduction and body mass changes that are independent of previous reproductive state. We illustrate how a strong context‐dependent fitness cost of reproduction can occur, despite a relatively fixed body mass cost of reproduction. This suggests that female reindeer display a very conservative energy allocation strategy, either aborting their reproductive attempt at an early stage or weaning at a relatively constant cost. Such a strategy might be common in species living in a highly stochastic and food limited environment. Abstract : In reindeer, demographic costs of reproduction result from the balance between constant body mass cost of reproduction but variable non‐reproductive body mass changes. The authors illustrate how a strong context‐dependent fitness cost of reproduction can occur despite a relatively constant body mass cost of reproduction.